Ancient Near Eastern art in context : studies in honor of Irene J. Winter - Cheng, Jack.; Feldman, Marian H.; Winter, Irene. (Culture and history of the ancient Near East,, 2007)
Through her published works and in the classroom, Irene J. Winter has served as a mentor for the latest generation of scholars of Mesopotamian visual culture. The various contributions to this volume in her honor represent a cross section of the state of scholarship today. Topics by the twenty authors include palatial and temple architecture, royal sculpture, gender in the ancient Near East, and interdisciplinary studies that range from the fourth millennium BCE to modern ethnography and cover Sumer, Assyria, Babylonia, Iran, Syria, Urartu, and the Levant. Reflections on Winter's scholarship and teaching accompany her bibliography. The volume will be useful for scholars who are curious about how visual culture is being used to study the ancient Near East.